Spuren der altägyptischen Gesellschaft Festschrift für Stephan J. Seidlmayer - Bußmann, Richard; Schiestl, Robert; Werning, Daniel A.; Hafemann, Ingelore (Zeitschrift für ägyptische Sprache und Altertumskunde - Beihefte, 2022)
The legacies of Old Egyptian society range from monumental pyramids to the microscopic traces of human activity, from stone inscriptions to novels. How can these things be put into a meaningful context, and what methods and questions would this require? This book brings together 28 contributions written in honor of Stephan J. Seidlmayer that try to provide up-to-date answers to these questions.